The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/f10070565
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Phylogeographic Analysis and Geospatial Methods to Infer Historical Dispersal Routes and Glacial Refugia of Liriodendron chinense

Abstract: Liriodendron chinense (Hemsl.), a Tertiary relic tree, is mainly distributed in subtropical China. The causes of the geographical distribution pattern of this species are poorly understood. In this study, we inferred historical dispersal routes and glacial refugia of this species by combining genetic data (chloroplast DNA (cpDNA), nuclear ribosomal DNA (nrDNA), and nuclear DNA (nDNA)) and geospatial data (climate and geology) with the methods of landscape genetics. Additionally, based on sequence variation at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 85 publications
3
13
1
Order By: Relevance
“…Although C. camphora is widely distributed in southern China, its origin is limited to East Asia and the Indochina Peninsula. The limited geographical distribution inhibits the gene exchange among populations and enhances genetic diversity within the population [33]. In addition, this study, together with the findings from Wu et al, showed lower genetic diversity of C. camphora in China than that of the Japanese population, which was not consistent with the results of Kameyama et al [2].…”
Section: Genetic Diversity Of C Camphoracontrasting
confidence: 93%
“…Although C. camphora is widely distributed in southern China, its origin is limited to East Asia and the Indochina Peninsula. The limited geographical distribution inhibits the gene exchange among populations and enhances genetic diversity within the population [33]. In addition, this study, together with the findings from Wu et al, showed lower genetic diversity of C. camphora in China than that of the Japanese population, which was not consistent with the results of Kameyama et al [2].…”
Section: Genetic Diversity Of C Camphoracontrasting
confidence: 93%
“…4A-C), which is consistent with the pattern of their natural geographical distribution [40,42,68]. This result is consistent with our previous research showing that there are shared haplotypes between the XN population and CW based on cpDNA and adaptive gene sequences [67]. This may be related to the geographical location of the XN population, which is closer to CE between CE and CW and may have experienced recent historical gene ow with CW.…”
Section: Discussionsupporting
confidence: 90%
“…For L. chinense, the long-term in situ refugia pattern may have caused genetic differentiation among the isolated populations [67]. In this study, the population structure analysis showed an obvious genetic divergence between CE and CW, but not the XN population (Figs.…”
Section: Discussionmentioning
confidence: 50%
“…Generally, the genetic diversity of species with a widespread distribution is higher than that of species with a narrow or endemic distribution [47,48]. Considering that the native habitant of C. camphora is widespread in the whole region of South China, it is not surprising that the genetic diversity in this study (Ho = 0.45 and He = 0.40) is much higher than that of other narrow or endemic species, such as Dalbergia odorifera (Ho = 0.28 and He = 0.37) [21], Gastrodia elata (Ho = 0.05 and He = 0.46) [24], and Ottelia acuminata (Ho = 0.28 and He = 0.37) [49].…”
Section: Genetic Diversity Of C Camphoramentioning
confidence: 99%